Nurcholish Madjid: Memadukan Kesalehan dan Politik - Idris Thaha (Studia Islamika, 2005)
Ann Kull, Piety and Politics: Nurcholish Madjid and His Interpretation of Islam in Modern Indonesia, Sweden: Lund University, 2005, xiv + 300 pp.This book is based on the dissertation of the author, Ann Kull, at the Department of History and Anthropology of Religion, Lund University, Sweden in November 2005. This book is one of a number of works that provide a thorough analysis of the thinking of one of Indonesia's foremost intellectuals Nurcholish Madjid (d. 2005) on matters concerning piety and politics. Kull's work, it could be said, is a reference work on Nurcholish's teachings.DOI: 10.15408/sdi.v12i2.592